Are parenting style and Mediterranean diet in children associated? - Buja, Alessandra; Miatton, Andrea; Zanovello, Anna; Brocadello, Filippo; Muhiddin, Marian Nur; Spreghini, Ilaria; Grotto, Giulia; Baldovin, Tatjana (Frontiers in Nutrition, 2025)
IntroductionThe Mediterranean diet (MD) is widely recommended as a healthy eating pattern for children because of its many benefits for growth, development, and long-term well-being. Eating habits during childhood are significantly influenced by parental behavior and may lead to lasting eating habits in later life. The purpose of this study is to examine the link between three different parenting styles (social, didactic, disciplinant) and children’s adherence to the MD.MethodsA total of 332 fifth-grade students, ages 10–12, participated in a cross-sectional survey as part of an educational intervention called “Le Buone Abitudini” [Good Habits]. The children’s mothers were asked to respond anonymously to a self-administered online multiple-choice questionnaire that investigated children’s adherence to the MD (using the KidMed score) and variables related to their lifestyles, behavioral characteristics, socioeconomic factors, and Parenting Styles Questionnaire (PSQ). Multivariable stepwise linear regression was performed to test the association between children’s KidMed score and parental adherence to three types of behavior: social, didactic, and disciplinant, adjusting for covariates.FindingsAccording to the KidMed score, 86.2% of children in the sample had medium or high adherence to the MD. Multivariable analysis revealed a direct correlation between didactic parenting style and increased compliance with MD (regression coefficient 0.95, p < 0.001).ConclusionThe present study emphasizes that parental behavior can significantly influence children’s adoption of healthy habits. A didactic parenting style that combines caring guidance with the enforcement of age-appropriate rules is most effective in enhancing children’s adherence to the MD. Health promotion programs should teach parents this aspect of education to equip them with the best tools for fostering healthy eating habits in their children.